2021
DOI: 10.1186/s12886-020-01799-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of optic disc area measured by confocal scanning laser tomography versus Bruch’s membrane opening area measured using optical coherence tomography

Abstract: Background Precise optic disc size measurements based on anatomically exact disc margins are fundamental for a correct assessment of glaucoma suspects. Computerized imaging techniques, such as confocal-scanning-laser-tomography (CSLT), which applies operator defined boundaries and optical-coherence-tomography (OCT), which incorporates an alternative detectable landmark (Bruch’s-membrane-opening (BMO)), have simplified the planimetry of the optic disc and BMO-area, respectively. This study’s obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although the thickness parameters measured by OCT are valuable in diagnosing glaucoma among high myopia, several aspects need to be considered when interpreting the results of OCT. First, due to the magnification effect of longer axial length in high myopic eyes, OCT will scan larger area than that in emmetropic eyes. The actual size of fundus dimension can be expressed as t = P * q * s, where t is the actual fundus dimension, s is the measurement obtained by OCT, P is the magnification factor for the imaging system, q is the magnification factor related to the eye 50. Note that RNFL becomes thinner to distant to optic disc in healthy eyes, thinning due to glaucoma or magnification will be challengeable to distinguish in this situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the thickness parameters measured by OCT are valuable in diagnosing glaucoma among high myopia, several aspects need to be considered when interpreting the results of OCT. First, due to the magnification effect of longer axial length in high myopic eyes, OCT will scan larger area than that in emmetropic eyes. The actual size of fundus dimension can be expressed as t = P * q * s, where t is the actual fundus dimension, s is the measurement obtained by OCT, P is the magnification factor for the imaging system, q is the magnification factor related to the eye 50. Note that RNFL becomes thinner to distant to optic disc in healthy eyes, thinning due to glaucoma or magnification will be challengeable to distinguish in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…The actual size of fundus dimension can be expressed as t = P * q * s, where t is the actual fundus dimension, s is the measurement obtained by OCT, P is the magnification factor for the imaging system, q is the magnification factor related to the eye. 50 Note that RNFL becomes thinner to distant to optic disc in healthy eyes, thinning due to glaucoma or magnification will be challengeable to distinguish in this situation. Also, it is more difficult to measure a thinner layer accurately in OCT. 51 Previous study indicated that the measurement of the RNFL thickness was significantly affected by ocular magnification and the measured value may be less than the actual thickness.…”
Section: Diagnostic Difficulties Of High Myopia Glaucoma With the Use...mentioning
confidence: 99%
“…While some authors report no correlation between HRT and OCT optic disc measurements [ 38 ], Cazana et al have recently demonstrated transferability of HRT measurements to an OCT-based BMOA assessment. They report a BMOA of ≥2.19 mm 2 to resemble the adequate threshold value for optic discs to be considered macrodiscs; however, they did not include microdiscs in their analysis [ 15 ]. Therefore, as definitive BMOA reference values for micro-, norm- and macrodiscs remain elusive, this study adhered to the traditional HRT division for optic discs size classification and added a 5% quantile approach in order to examine extreme optic nerve heads.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, this attribution of optic discs to one group has been based on fundoscopic assessment or on measurement results of confocal scanning laser tomography (CSLT). In recent years, studies using OCT for the characterization of optic disc morphology have demonstrated that approaches based on Bruch´s membrane opening area (BMOA) can be used instead [ 7 , 15 , 16 , 17 ]; however, categorization and thresholds for micro- and macrodiscs are still not universally defined.…”
Section: Introductionmentioning
confidence: 99%